المعرفة الإسلامية ودورها في تنمية فكر البشرية دراسة تحليلية: Islamic knowledge and its role in developing human thought: An Analytical Study - Moustapha Mbacke , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث هدفت الدراسة إلى التّعرّف على المعرفة الإسلامية ودورها في تنمية فكر البشرية. وتكمن مشكلة الدّراسة في غياب تطبيق المعرفة الإسلامية وإهمال ما أمر الله عز وجل في القرآن الكريم والسنة النبوية المطهرة. وتبرز أهمية الدّراسة في تسليط الضوء على المعرفة الإسلامية ودورها في تنمية فكر البشرية. ولقد اتبعت الدراسة المنهج التحليلي لتحليل المعرفة الإسلامية ودورها في تنمية فكر البشرية. كما اتبعت الدراسة المنهج الاستقرائي لاستقراء نصوص القرآن الكريم والسنة النبوية المطهرة الدالة على المعرفة الإسلامية، كما اتبعت الدّراسة المنهج المقارن لمقارنة المعرفة الإسلامية بالمعرفة التقليدية وتأثير كلّ منهم على تنمية فكر البشرية. ولقد توصلت الدّراسة إلى العديد من النتائج من بينها أنّ هناك تأثيرًا مباشرًا للمعرفة الإسلامية ودورها في تنمية فكر البشرية. ولقد أوصت الدراسة بضرورة الاهتمام بالمعرفة الإسلامية وإعادة تشكيلها بما يضمن تنمية وتطوير فكر البشرية. ABSTRACT The paper aims to identify Islamic knowledge and its role in developing human thought. The problem of the study lies in the absence of application of Islamic knowledge and the neglect of what God Almighty has commanded in the Holy Qur’an and the Sunnah of the Prophet. The importance of the study is highlighted in shedding light on Islamic knowledge and its role in developing human thought. The study adopts the analytical approach to analyze Islamic knowledge and its role in developing human thought. It employs the inductive approach to extrapolate the texts of the Holy Qur’an and the Sunnah of the Prophet that symbolize Islamic knowledge. It also uses the comparative approach to compare Islamic knowledge with traditional knowledge and the impact of each of them on the development of human thought. The major finding of the study is that, there is a direct impact of Islamic knowledge in developing human thought. It recommends that there is need to pay attention to Islamic knowledge and reshape it in a way that ensures development of human thought.